Application of eCommerce Technology as Online Sales Media - Widhy Wahyani; Sanny Andjar Sari (NAROTAMA UNIVERSITY, 2022)
The increasingly rapid use of the internet as an impact of information technology infrastructure which in fact is able to encourage the birth of a new paradigm in the process, namely the use of the internet and information and communication technology infrastructure. In the midst of the widespread use of e-commerce technology today, it has also penetrated the MSME business sector. The purpose of this research is to implement e-commerce technology that functions as an online sales medium, to find out the obstacles faced in implementing e-commerce technology, and to know the advantages and disadvantages of e-commerce implementation. The object of this research is MSME Various Foods